Evaluation of Ecological Water Conservancy Benefits for Lakeside Cities Based on Principal Component Analysis - GU Xiaohan; ZHU Shijie; MAO Jinqiao (Renmin Zhujiang)
Lakeside cities are important intersection areas of natural land,lakes and urban ecology.Poyang Lake plays an important role in regulating the water level of the Yangtze River,conserving water resources,improving local climate and maintaining water security.In order to objectively and comprehensively measure the ecological water conservancy benefits of the lakeside cities around the Poyang Lake,taking the Gongqingcheng City as a typical case and the statistical analysis as a basis,this paper puts forward the evaluation index system qualitatively and quantitatively from three aspects of economic benefits,social benefits and ecological benefits,and constructs the evaluation model by the principal component analysis method.The results show that the score of ecological water conservancy benefits of the Gongqingcheng City in 2019 is 1.253 8,the ecological quality grade is Class III,the regional economy is well developed,and the ecological and social benefits are remarkable,which are consistent with the current ecological status of the Gongqingcheng City.Therefore,the model is featured with good applicability and rationality.